Sustainability Reporting and Financial Performance: The Moderating Role of Chief Executive Officer (CEO) Characteristics and Ownership Concentration - Dewi, Meyviva Isnaini; Hasanudin, Agus Ismaya; Soleha, Nurhayati (Management Science Research Journal, 2025)
This study aims to examine the effect of sustainability reporting on financial performance by considering the role of CEO characteristics and ownership concentration as moderating variables. This study also adds leverage and company size as control variables. The independent variable of sustainability reporting is measured based on the 2016 GRI standard and the 2021 GRI standard. The dependent variable of financial performance is measured by Tobin's Q. The moderating variables of CEO characteristics are measured by CEO education and CEO tenure. This study focuses on consumer non-cyclical sector companies on the Indonesia Stock Exchange during the 2020-2023 period. This study is a quantitative research using secondary data from the Indonesia Stock Exchange and company websites. Purposive sampling technique was used to take samples, so that 110 observation samples were obtained. Hypothesis testing was tested through Moderated Regression Analysis with the help of IBM SPSS v25 software. The results of this study prove that sustainability reporting has a positive effect on financial performance, CEO education positively moderates the effect of sustainability reporting on financial performance, CEO tenure does not moderate the effect of sustainability reporting on financial performance, and ownership concentration negatively moderates the effect of sustainability reporting on financial performance.